Work pressure management in Islamic educational administration: insights from Fathi Abu Nasr - Atep Muhammad Lutfi; Mukhamad Najikh; Iska Fatmawati; Ateng Ruhendi; Izzuddin Musthafa (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study examined work pressure management within Islamic educational administration by bringing Fathi Abu Nasr’s ideas into dialogue with contemporary management theory. The study addressed a gap in the literature: modern discussions of organizational stress are largely framed through psychological and behavioral perspectives, while systematic comparative analyses that connect Islamic educational administration with contemporary management remain limited. Using qualitative library research and comparative content analysis, the study analyzed Abu Nasr’s educational management framework alongside modern perspectives on stress regulation, emotional intelligence, and organizational support. The findings show that both perspectives emphasize self-regulation, motivation, and supportive environments, but differ in their epistemological foundations and ultimate aims. Abu Nasr’s framework grounds work pressure management in spiritual discipline, ethical responsibility, and accountability before God, whereas contemporary management primarily approaches it as a matter of adaptation, effectiveness, and well-being. Based on this comparison, the study proposes a holistic model of work pressure management that integrates spiritual regulation, ethical leadership, cognitive-behavioral adaptation, and organizational support. This model contributes to Islamic educational administration by linking productivity, psychological resilience, and transcendental accountability in a more integrated conceptual framework.